ANALISIS SPASIAL KEJADIAN DEMAM BERDARAH DENGUE DI WILAYAH KERJA PUSKESMAS BOJONG RAWALUMBU KOTA BEKASI TAHUN 2021-2022 - Wafa Haniyati Zahra (2023)
The increase in cases of Dengue Hemorrhagic Fever (DHF) in the working area of Puskesmas Bojong Rawalumbu, Bekasi City, continues to occur. In 2021, there were 146 cases, making DHF the third highest disease in the area. This study was conducted to determine the spatial distribution of DHF incidents based on gender and age groups, as well as to assess the Breeding Index (BI), population density, and DHF incidence prevalence in the working area of Puskesmas Bojong Rawalumbu in 2021-2022. This research is a descriptive study, where univariate analysis was used to determine the frequency distribution of DHF cases, and spatial analysis was employed to visualize and depict the distribution map of DHF incidents.The findings of this study reveal that there were 146 DHF cases in 2021, with a BI of 96%. In 2022, the number of cases decreased to 75, with a BI of 97%. DHF incidents were more prevalent among males and the age group of 5-25 years old. The prevalence of DHF in 2021 was 13.42%, which decreased to 7.07% in 2022. DHF cases in the working area of Puskesmas Bojong Rawalumbu, Bekasi City, from 2021 to 2022 mostly occurred in areas with high population density, predominantly affecting children and adolescents. Based on these findings, it is recommended to implement DHF prevention programs that can effectively reduce the incidence of DHF in these age groups..